ANALISIS VALUE ENGINEERING PADA PROYEK PEMBANGUNAN PUSKESMAS MEDAN JOHOR - Liberty Herinius Ginting; Ahmad Bima Nusa (Buletin Utama Teknik, 2023)
In a project that has a large cost, there are several parts of the work whose costs have a large influence on the overall project cost. The cost of these parts of the work is influenced by several aspects, including in terms of materials, materials and dimensions, work methods, number of workers, execution time and others. The construction project for the Medan Johor Health Center building is to build a health center that meets national standards with a budget of approximately Rp. 3.8 M. This is related to the selection of designs and materials used in planning the construction of the building. Value engineering is an organized method for analyzing a problem with the aim of obtaining the desired functions with optimal costs and final results. The purpose of this paper is to determine the cost savings obtained from the application of Value Engineering and to determine the cost savings achieved before and after Value Engineering is carried out. Value Engineering analysis was carried out on the construction project of the Medan Johor Health Center which is located in the Medan Johor area. From the results of the Value Engineering analysis on the Medan Johor public health center construction project by looking at the use of materials in the work of the Column and Beam Formwork, floor and wall ceramic work, and wall plastering work, it can be concluded that savings from the calculation of Life Cycle Cost.